Approaches between cinema and geography to think the environmental issue: a geographical analysis of the movie “The constant garde" - Pimenta, Thiago Albano (Geografares, 2014)
This paper deals with possibilities of links between scientific language and cinematic language. Geography as a discipline that includes several knowledge can be one of the links to these approaches, understanding that it is increasingly necessary to broaden the ways of doing and thinking science bringing practices and experiences that everyday presents. Thus we can think of geographical analysis of cinema as a form of dialogue between science and cultural practices that express the multiplicity of geographical space.Keywords: geography; cinema; environmental issue.